2016
DOI: 10.1177/0022034516659642
|View full text |Cite
|
Sign up to set email alerts
|

PIN1 Suppresses the Hepatic Differentiation of Pulp Stem Cells via Wnt3a

Abstract: This study aimed to investigate the role of PIN1 on the hepatic differentiation of human dental pulp stem cells (hDPSCs) and its signaling pathway, as well as the potential therapeutic effects of hDPSC transplantation and PIN1 inhibition on CCl (carbon tetrachloride)-induced liver fibrosis in mice. The in vitro results showed that hepatic differentiation was suppressed by infection with adenovirus-PIN1 and promoted by PIN1 inhibitor juglone via the downregulation of Wnt3a and β-catenin. Compared with treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…Combination with functional innervation and vascularization appears more persuasive for functional pulp regeneration. 107 118 Additionally, predifferentiated PSCs, including hepatocytes, 125 myocytes, 128 osteoblasts, 143 islet-like cell cluster, 45 and keratocytes, 137 Table 3, such as calvarial defect, 110 cerebral ischemia, 116,117 and limbal stem cell deficiency, 38 It was also reported that SHED are capable of differentiating into hepatocyte-like cells directly without fusion in mouse models of carbon tetrachloride-induced liver fibrosis, therefore recovering liver disfunction. 41 In a recent mouse in vivo study, 12…”
Section: Exogenous Recombinant Growth Factors a Variety Of Exogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination with functional innervation and vascularization appears more persuasive for functional pulp regeneration. 107 118 Additionally, predifferentiated PSCs, including hepatocytes, 125 myocytes, 128 osteoblasts, 143 islet-like cell cluster, 45 and keratocytes, 137 Table 3, such as calvarial defect, 110 cerebral ischemia, 116,117 and limbal stem cell deficiency, 38 It was also reported that SHED are capable of differentiating into hepatocyte-like cells directly without fusion in mouse models of carbon tetrachloride-induced liver fibrosis, therefore recovering liver disfunction. 41 In a recent mouse in vivo study, 12…”
Section: Exogenous Recombinant Growth Factors a Variety Of Exogenousmentioning
confidence: 99%
“…Differentiated dopaminergic neuron‐like SHED have been reported to survive in striatum of PD mice, significantly improve dopamine level and fiber sprouting in contrast to undifferentiated SHED and enhance neurological recovery . Additionally, predifferentiated PSCs, including hepatocytes, myocytes, osteoblasts, islet‐like cell cluster, and keratocytes, have been administered with therapeutic benefits in animal models for liver fibrosis, muscular dystrophy, calvarial bone defect, diabetes, and corneal trauma, respectively. It is indicated that transplantation of preinduced or predifferentiated PSCs appears more efficacious and more applicable to enhance functional recovery as compared with undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, for restoration of liver mass after hepatectomy both systemic and coordinated changes are needed in gene expression. These starts guiding regenerative responses, activation of progenitor cells, and proliferation of quiescent hepatocytes [112]. The chronic and repeated liver injuries are caused by alcohol, and HBV, HCV, or other pathogens.…”
Section: Hepatocytesmentioning
confidence: 99%
“…SOT recipients also face high mortality. Hence, an effective donor screening and prophylaxis should be followed in high-risk SOT recipients to decrease morbidity and mortality [177]. Liver from aged and diseased patients should be avoided.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…The pulp originates from the neural crest of the embryo. hDPSCs readily differentiated into mesenchymal-lineage cells (osteocytes, chondrocytes, and adipocytes) and endodermal-lineage cells (hepatocytes and pancreatic cells), as well as neuro-ectodermal cells 6 , 14 , 16 , 17 , 20 , 21 , 22 . In addition, hDPSCs displayed remarkable functional hepatogenic differentiation potential in vitro and regeneration of injured liver tissues in vivo 2 , 6 , 18 - 22 .…”
Section: Introductionmentioning
confidence: 99%